DIGITAL LEADERSHIP, COMPETENCE, ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE PRATAMA TAX SERVICE OFFICE (KPP) IN ACEH PROVINCE - Rizal Karmana; Jullimursyida; Marbawi (CV. RADJA PUBLIKA, 2024)
This study aims to analyze the influence of Digital Leadership, Competence on Employee Performance with Job Satisfaction as an Intervening Variable at the Tax Service Office of Aceh Province, the dependent variable of this study is digital leadership and the competency for the independent variable is employee performance , for the intervening variable is job satisfaction. The population in this study is 265 personnel of the Tax Service Office of Aceh Province. The sampling technique used proportionate stratified random sampling and a sample of 170 respondents who were employees at the Tax Service Office of Aceh Province was obtained, the research method used was a quantitative method, for the data analysis method using Structural Equation Modeling (SEM). The results of this study show that digital leadership and competence have a significant effect on job satisfaction, furthermore, digital leadership, competence and job satisfaction have a significant effect on the performance of employees of the Aceh Provincial Tax Service Office. This study shows that job satisfaction is the most dominant variable affecting the performance of employees of the Tax Service Office of Aceh Province. In this study, digital leadership and competence have a significant effect on employee performance through job satisfaction as an intervening variable, it can be concluded that job satisfaction functions as a partial mediation between exogenous and endogenous variables.